To rewrite the equations for height by subtracting \(2t\) from both sides, we start with the two initial equations given:
-
For Plant A: \[ h = 4 + 2t \]
-
For Plant C: \[ h = 8 + 2t \]
Now, let's subtract \(2t\) from both sides for both equations:
-
For Plant A: \[ h - 2t = 4 \]
-
For Plant C: \[ h - 2t = 8 \]
Now, you can see that the relationship becomes:
-
Height of Plant A: \[ h - 2t = 4 \]
-
Height of Plant C: \[ h - 2t = 8 \]
To summarize:
- Height of Plant A becomes \(h - 2t = 4\)
- Height of Plant C becomes \(h - 2t = 8\)
If you need anything else or further clarification, let me know!